Marketing digital para el posicionamiento de la Empresa CRUZPLAST S.A sector Vía Daule, Guayaquil - Cruz Villamar, Genesis Pamela (2023)
This degree work focuses on the positioning problem of the company CruzPlast S.A., plastic covers in Guayaquil, Ecuador. Throughout its 10 years of existence, the absence of a presence in digital media has affected its competitiveness in the market. Chapter one presents the problem, its relevance, the general and specific objectives. Chapter two reviews background, theories related to digital marketing and positioning. Chapter three details the mixed approach used, with data collection techniques, interviews with the Manager of CruzPlast S.A and an expert in Digital Marketing. Chapter four summarizes the objectives of the proposal and justifies its approach to design Digital Marketing strategies. The central theme is to improve the positioning of CruzPlast S.A. The lack of promotional strategies and a strong corporate image have kept the company in an unfavorable position. The absence of an effective marketing strategy has affected its visibility and preference in the market, while the lack of advertising content in digital media has limited its recognition. The proposal seeks to design digital marketing strategies to improve visibility, attract customers, increase sales and strengthen the relationship with current customers. The objectives include positioning in the digital environment, competitive advantages, customer acquisition and loyalty, increased sales and improvement of the brand's reputation. In summary, this thesis aims to solve the positioning challenge of CruzPlast S.A through the implementation of Digital Marketing strategies.